2019
DOI: 10.1080/17461391.2019.1603327
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shoe drop on running kinematics and kinetics in female runners

Abstract: This study investigated the effects of shoe drop on lower limb kinematics and kinetics in female runners. Fifteen healthy female runners ran on a 15-m runway at their preferred speed with three different shoe-drop conditions: 0 (D 0 ), 6 (D 6 ) and 10 (D 10 ) mm. Three-dimensional marker positions and ground reaction forces were recorded to analyse kinetic and kinematic parameters using zero-(0D) and one-dimensional (1D) metrics (statistical parametric mapping, SPM). Regarding 0D parameters, significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 44 publications
5
16
0
Order By: Relevance
“…At initial contact and during the early standing phase, ankle dorsiflexion was significantly weakened when running in shoes without a drop, suggesting the pre-activation of the plantarflexion muscles was greater. The higher vertical loading rate observed in shoes without a drop was in accordance with previous studies that showed a significant positive correlation between the amplitude of pre-activation of the gastrocnemius and the vertical impact peak [7,29]. Combined with a previous study, the results of current study may have significance in preventing pathologies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…At initial contact and during the early standing phase, ankle dorsiflexion was significantly weakened when running in shoes without a drop, suggesting the pre-activation of the plantarflexion muscles was greater. The higher vertical loading rate observed in shoes without a drop was in accordance with previous studies that showed a significant positive correlation between the amplitude of pre-activation of the gastrocnemius and the vertical impact peak [7,29]. Combined with a previous study, the results of current study may have significance in preventing pathologies.…”
Section: Discussionsupporting
confidence: 92%
“…Our study compared running shoes that varied only in terms of the drop and showed that running in shoes with large drops did not change the vertical impact force but significantly decreased the vertical loading rate. Previous studies, in accordance with our study, have shown a decrease in the vertical loading rate when increasing the drop of running shoes or the foot inclination angle [7,28]. At initial contact and during the early standing phase, ankle dorsiflexion was significantly weakened when running in shoes without a drop, suggesting the pre-activation of the plantarflexion muscles was greater.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A Statistical Parametric Mapping (SPM) technique [39,40] assessed the main effects of 'running shoes' and 'running speed 'factors and their interaction, and SPM tests were calculated with the SPM1D v0.4 for MATLAB (www.spm1d.org (accessed on 1 March 2021), [39]). The significance level was set at 0.05 for all statistical tests.…”
Section: Discussionmentioning
confidence: 99%